ABU HAMID AL-GHAZĀLĪ’S THOUGHTS ON THE DICHOTOMY OF ULAMA AND THE CLASSIFICATION OF KNOWLEDGE (STUDY OF IHYA ‘ULUM AL-DIN BOOK) - Muhammad Solikhudin (Prodi Studi Agama-agama Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2021)
This paper analyzes al-Ghazālī’s thoughts, especially in the discussion of the categorization of scholars and the groupings of knowledge which he offers in the book Ihyā ‘Ulūm al-Dīn. As a scientist of Islamic Studies, alGhazālī was able to present this discussion in an interesting and profound way. He stated in his creation that scholars are divided into two. First is the counterfeit ulama called al-sū’. The second is the ulama who is true (hereafter). Likewise with science, al-Ghazālī divides knowledge globally into two things, namely knowledge that is fardu ‘ain and fardu kifayah. As an ulama who is an expert in all scientific fields who eventually pursues the field of Sufism, it can be seen how much he presents the book Ihyā ‘Ulūm al-Dīn with a distinctively Sufistic nuance. It does not seem patronizing and always interesting to read, especially for lovers of the world of Sufism. The Ihyā ‘Ulūm al-Dīn is divided into four parts. First, a quarter about Worship. Second, a quarter about habits. Third, a quarter about destruction. Fourth, a quarter about secrets/feelings. Even so, it does not rule out the possibility in this work, for insiders and outsiders to carry out further elaboration and various other intellectual activities, in order to present a more interesting work in the present and future.